UJI KOMPETENSI DAN PROGRAM SERTIFIKASI BAGI PENDIDIK DAN TENAGA KEPENDIDIKAN PENDIDIKAN LUAR SEKOLAH - Anan Sutisna (Jurnal Ilmiah Visi, 2007)
The quality of out-of-school education can be improved not only by providing enough facilities and budget or improving the curriculum but also and the most important is by developing the quality of the human resources such as facilitators, instructors, partners, or tutors. This article discusses how competence certification can be used as a means of improving the quality of educators in outofschool education. The competence certification is to be based on the basic competence, competence standards, and competence indicators which are offered in this article.